2015
DOI: 10.18768/ijaedu.53675
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of L1 Overuse in L2 Learning: Evidence From Three Case Studies

Abstract: Foreign language teaching based on the mother tongue has been the traditional vehicle of instruction in Russian classrooms from the primary to high school levels, at language schools as well in teacher-formation at pedagogical institutes as is evidenced by the results of information obtained through interviews to teachers, observation of the students' in-class behavior and revision of textbooks produced by national authors. Grounded on data (transcripts, essays, and real class examples) gathered during five ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…One of the issues complicating discussions about L1 use in the L2 classroom is the acceptable amount of L1 in the L2 classroom, or L1 "overuse" (Fernández, 2015) versus "judicious use" (Lo, 2015). Turnbull (2001), for example, proposed that teachers who use the L2 for less than 25% of class time may be relying too heavily on the L1 and depriving their students of valuable L2 input.…”
Section: L1 Overuse Versus Judicious Usementioning
confidence: 99%
See 2 more Smart Citations
“…One of the issues complicating discussions about L1 use in the L2 classroom is the acceptable amount of L1 in the L2 classroom, or L1 "overuse" (Fernández, 2015) versus "judicious use" (Lo, 2015). Turnbull (2001), for example, proposed that teachers who use the L2 for less than 25% of class time may be relying too heavily on the L1 and depriving their students of valuable L2 input.…”
Section: L1 Overuse Versus Judicious Usementioning
confidence: 99%
“…All in all, the abovementioned studies reinforce that L2 teachers vary a lot in their L1 usage and that sometimes their reported and actual usage differ. Still, a common understanding across the studies is that unnecessary or excessive L1 use that hampers L2 development can be considered L1 overuse, while purposeful L1 use that aligns with L2 learning objectives can be considered judicious or selective use (Fernández, 2015;Lo, 2015;Macaro, 2005;Turnbull, 2001).…”
Section: L1 Overuse Versus Judicious Usementioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, negative or hindering effects of overuse of L1 were prevailed by minimizing learners' exposure to L2 (Almoayidi, 2018;Fernandez, 2015;Khati, 2011, p. 48). To this end, Littlewood and Yu (2011) focused on the ways of maximizing the use of target language in EFL classrooms without downsizing the use of L1 for developing foreign language learning (p. 73).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it should be pointed out that research [1], [2], [3], [4] has shown that classroom communication, the excessive use of the mother tongue, and error correction in addition to the challenges posed by new learning environments call for a change of mentality and practices in FLE practitioners and learners. These conditions imposed by, for instance, the advent of IT, the presence of the multiple language repertoires performed in international classrooms at the universities, and the resulting multicultural contact in and outside campus [5] demand proactive language policies in which not only the educational environment but also the city as whole is considered.…”
Section: Introductionmentioning
confidence: 99%